Lessons to be learned: how a comprehensive neurobiological framework of atypical reading development can inform educational practice. (August 2016) - Ozernov-Palchik, Ola; Yu, Xi; Wang, Yingying; Gaab, Nadine
Highlights: Genetic, neural, cognitive, and environmental risks for dyslexia are identified. Evidence supports a multi-componential framework for dyslexia etiology. Implications of neuroscientific findings for educational practice are discussed. Abstract : Dyslexia is a heritable reading disorder with an estimated prevalence of 5–17%. A multiple deficit model has been proposed that illustrates dyslexia as an outcome of multiple risks and protective factors interacting at the genetic, neural, cognitive, and environmental levels. Here we review the evidence on each of these levels and discuss possible underlying mechanisms and their reciprocal interactions along a developmental timeline. Current and potential implications of neuroscientific findings for contemporary challenges in the field of dyslexia, as well as for reading development and education in general, are then discussed.